MY SAY: The World Cup - more than just soccer - Abd Razak, Dzulkifli (2010)
The World Cup is finally over! This time there were many winners and firsts. There was victory for Spain — the world's best team — and also for South Africa, the first country on the African continent to host the event. The tournament was a great success although the country initially faced scepticism from many quarters. True, it received some bad press, especially with regard to security, but its 40,000odd dedicated police force managed to keep the problem from worsening.